2011
DOI: 10.1097/pep.0b013e318227b737
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lower Body Positive Pressure Supported Treadmill Training for Children With Cerebral Palsy

Abstract: It is feasible to use LBPPS treadmill training to improve the walking performance, balance, and strength of children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 50 publications
2
50
1
Order By: Relevance
“…In-place resistance to perturbation and forward, backward, and lateral responses to "push and release" (14)(15)(16)(17)(18) Sensory 29 All other materials were used in accordance with BESTest written standards. The stair height was 17 cm, and the obstacle (2 stacked shoe boxes) height was 25 cm.…”
Section: Sectionmentioning
confidence: 99%
“…In-place resistance to perturbation and forward, backward, and lateral responses to "push and release" (14)(15)(16)(17)(18) Sensory 29 All other materials were used in accordance with BESTest written standards. The stair height was 17 cm, and the obstacle (2 stacked shoe boxes) height was 25 cm.…”
Section: Sectionmentioning
confidence: 99%
“…In adults, the original, or Full-BESTest, has been shown to assist in identifying specific balance deficits [32] and in measuring changes in postural control before and after intervention [33]. In children, one preliminary study involving children with CP has supported the potential use of the Full-BESTest with paediatric populations [34]. However, there is a need to establish psychometric data and clinical utility for children with and without disabilities before more widespread use [26,28] [35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, BWSTT can be used to assist children with Down syndrome to achieve their walking motor milestone sooner (Ulrich, D. A, Ulrich, B. D., Angulo-Kinzler, & Yun, 2001). Moreover, several studies have shown that BWSTT can result in improvements in the walking speed, walking endurance, and gross motor function of children with cerebral palsy (CP) (Cherng, Liu, Lau, & Hong, 2007;Dodd & Foley, 2007;Kurz, Corr, Stuberg, Volkman, & Smith, 2011a;Kurz, Stuberg, DeJong, 2011b;Kurz, Wilson, Corr, Volkman, 2012;Mattern-Baxter, Bellamy, & Mansoor, 2009). These encouraging results infer that supporting the body weight during treadmill training may be a task-specific therapeutic modality that provides essential afferent feedback for neural connections that govern a successful stepping pattern.…”
Section: Introductionmentioning
confidence: 95%